Portrayals of Immigrants and Refugees in U.S. News Media: Visual Framing and its Effect on Emotions and Attitudes. Issue 4 (2nd October 2019) - Parrott, Scott; Hoewe, Jennifer; Fan, Minghui; Huffman, Keith
Abstract : This research explores the effects of visual representations of immigrants and refugees in U.S. news outlets. Study 1 examined news photographs about immigrants and refugees that were shared on Twitter by regional news outlets in all 50 states. Most photos contained either a human interest frame, featuring immigrants and refugees as everyday people, or a political frame, showcasing politicians. Study 2's experiment determined the effects of these visuals on participants' emotions and, in turn, their attitudes toward immigrants and refugees. The political frame increased negative emotions, leading to negative attitudes. The human interest frame increased positive emotions, enhancing positive attitudes.